Lifting Moving Management with Role Play Method On Volunteers Mojokerto Tanggap Bencana (MTB) - Heni Fauziah; Agus Haryanto; Eka Nur So’emah; Mufarika Mufarika (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Lifting and moving disaster victim management skills are important competencies for volunteers. Incorrect techniques can aggravate the victim's injury, but it is also at high risk of causing back injury to volunteers. Mojokerto Tanggap Bencana (MTB) volunteers need effective training methods to ensure safe mastery of techniques. The Role Play method was chosen because it offers a simulation of real situations of hands-on practical learning. analyzes the effect of the application of the Role Play method on the improvement of the knowledge and skills of lifting moving victims in MTB volunteers. This study used a quasi-experimental design of One-Group Pretest-Posttest with a total sampling technique of 56 active MTB volunteers. The intervention provided was lifting moving training using the Role Play method. Knowledge was measured using an intervention pre-post test questionnaire . Skills were measured using a standard checklist on a score scale of 0-100. Data analysis was carried out by paired t-test. The implementation of lifting moving management by volunteers prior to role play training is still low, with nearly half of respondents (48%) rated